Avaliação de dois sistemas forrageiros sob pastejo com vacas leiteiras - Steinwandter, Edilene (2009)
The objective of this work was evaluate two pasture-based systems (PS) with elephantgrass (Pennisetum purpureum Schum.), ryegrass (Lolium multiflorum Lam.), and spontaneous growth species varying in one system, the mixture with white clover (Trifolium repens L.) and, in the other system, with forage peanut (Arachis pintoi Kraprov & Gregory), handled under rotational grazing. The experiment was done from April 24th, 2007 to April 30th, 2008, totalizing 371 days. In order to evaluate were used four paddocks with 0.25 ha each one, where the elephantgrass was established in lines with a distance of 4 m between lines. In the winter period, in space between lines, was established the ryegrass and in two paddocks the white clover was sown and, in the other two, the forage peanut was preserved, which had already been established. The experimental design was completely randomized, with two treatments (pasture-based systems), two replicates (paddocks) and in subdivided parcels in the time (grazing cycles). The grazing were fertilized with 100, 60 and 100kg/ha de N, P2O5 and K2O, respectively. As experimental animals were used Holstein cows, in lactation, receiving 6 and 5 kg of complementary concentrate feed in winter and summer periods, respectively. The cows live weight was 514±35.9 kg and mean milk production of 20.80±2.23 kg/day. During the evaluation 11 grazing were done, six in the winter period, defined by ryegrass, and 5 in the summer period where the pre and post grazing were analyzed; the botanical compositions of grazing and structural of elephantgrass, ryegrass and legumes; accumulation rates and of disappearance of forage mass; stocking rate and pasture chemical composition (by samples of grazing simulation). The results show that the appraised botanical composition, in each treatment, contributed to compensate the offer and the forage chemical composition during the year. It was verified a better performance in the pasturebased system, using the forage peanut, considering the mean of the accumulation taxe and of disappearance of forage mass. Pasture-based systems showed similar chemical composition, indicating, the need of improving pasture-based systems to raise the pasture mass production at the start winter period, mainly the legumes contribution.